Talent identification and selection in sport - Malina, R. M. (1997)
Most parents would like to see their child/children experience success in sport. Some may even want to see their child excel at more elite levels, and perhaps attain national and international recognition. The progression from initial youth sport experiences to more elite levels is complex. It involves some degree of identification and selection of talented individuals at virtually all levels of youth sports. However, the process may also involve more formal identification and selection of individuals who presumably have the skill, physical, and behavioral requisites for success in a given sport. Community-Based Youth Sports Programs Elite Programs Eastern European Selection Programs Problems with Selection Programs Early Identification and Success in the Future Parents of Elite Young Athletes